Psychophysiological states and special performance of boxers with different styles of fight - V.V. Aksutin; G.V. Korobeynikov (H.S. Skovoroda Kharkov National Pedagogical University, 2014)
Purpose : The style of the fight is one of the important factors that affect the quality of the arts in boxing. Particularly important factor in the modern boxing are the mental processes that are involved in forecasting and analyzing the situation that arises in the ring and are associated with cognitive functions. Purpose - to examine the psychophysiological state and a special performance for skilled boxers with different styles of input match. Material : 22 highly qualification boxer aged 18-23 years were studies. The absolute and the relative strength of serial and single strikes were studied. Definition of special performance and power strokes performed on a special simulator. Recorded the absolute and relative strength of serial and single strikes. Results : The results show that the attacking style of the fight in boxing is accompanied by the presence of a high level of efficiency, reduction of fatigue, anxiety, and depending on the condition of vegetative functions. Showed a reduction in the growth of autonomy and heteronomy in the structure of psycho-physiological state of boxers with the attacking style of the fight, which indicates the presence of compromise and avoidance of external failures. Conclusions : Boxers with attacking style of fight characterized by high values of the left side impact forces and reduce the values of the right direct strike force, compared with boxers protective style of fight.